3D porous cellulose/polyaniline aerogel composite as a high-performance electrode for selective electrosorption of rhenium - Ruichen Ma; Boxiao Zhao; Xiling Sun; Zhenning Lou; Junshuo Cui; Haibiao Yu; Yuejiao Wang; Weijun Shan; Xiaogeng Feng; Ying Xiong (Water Research, 2026)

Dietary fiber-bound polyphenols in Canavalia gladiata seed coat: Optimization of conditions, identification and bioactivity assessment of acid, alkaline, and enzymatic extraction - Yue Qiu; Jiayan Xie; Jing Liang; Jianhua Xie; Yi Chen; Xiaobo Hu; Nan Sun; Xiling Wang; Qiang Yu (Food Chemistry, 2026)

A preliminary study on estimating soil thickness on karst dolomite slopes using ground gamma radiation dose rate in Southwest China - Xinbao Zhang; Yuemin Yue; Liang Shi; Lu Wang; Shuai Yuan; Xiling Zhang; Mingming Sun; Yi Zeng; Yunqi Zhang; Hongyan Liu; Kelin Wang (CATENA, 2025)

A novel Zn2+ probe for fluorescent monitoring of drug and E6/E7 protein interaction in living cells - Zhenzhen Xie; Lan Yu; Zuoping Li; Na Zhao; Shiwan You; Zhihao Zhao; Jindi Dou; Xiling Deng; Shiguo Sun (Analytica Chimica Acta, 2025)

Short-term residential exposure to air pollution and risk of acute myocardial infarction deaths at home in China - Jian Cheng; Hao Zheng; Jing Wei; Cunrui Huang; Hung Chak Ho; Shengzhi Sun; Dung Phung; Ho Kim; Xiling Wang; Zhongliang Bai; Mohammad Zahid Hossain; Shilu Tong; et al. (Environmental Science and Pollution Research, 2023)
Air pollution remains a major threat to cardiovascular health and most acute myocardial infarction (AMI) deaths occur at home. However, currently established knowledge on the deleterious effect of air pollution on AMI has been limited to routinely monitored air pollutants and overlooked the place of death. In this study, we examined the association between short-term residential exposure to China’s routinely monitored and unmonitored air pollutants and the risk of AMI deaths at home. A time-stratified case-crossover analysis was undertaken to associate short-term residential exposure to air pollution with 0.1 million AMI deaths at home in Jiangsu Province (China) during 2016–2019. Individual-level residential exposure to five unmonitored and monitored air pollutants including PM 1 (particulate matter with an aerodynamic diameter ≤ 1 μm) and PM 2.5 (particulate matter with an aerodynamic diameter ≤ 2.5 μm), SO 2 (sulfur dioxide), NO 2 (nitrogen dioxide), and O 3 (ozone) was estimated from satellite remote sensing and machine learning technique. We found that exposure to five air pollutants, even below the recently released stricter air quality standards of the World Health Organization (WHO), was all associated with increased odds of AMI deaths at home. The odds of AMI deaths increased by 20% (95% confidence interval: 8 to 33%), 22% (12 to 33%), 14% (2 to 27%), 13% (3 to 25%), and 7% (3 to 12%) for an interquartile range increase in PM 1 , PM 2.5 , SO 2 , NO 2 , and O 3 , respectively. A greater magnitude of association between NO 2 or O 3 and AMI deaths was observed in females and in the warm season. The greatest association between PM 1 and AMI deaths was found in individuals aged ≤ 64 years. This study for the first time suggests that residential exposure to routinely monitored and unmonitored air pollutants, even below the newest WHO air quality standards, is still associated with higher odds of AMI deaths at home. Future studies are warranted to understand the biological mechanisms behind the triggering of AMI deaths by air pollution exposure, to develop intervention strategies to reduce AMI deaths triggered by air pollution exposure, and to evaluate the cost-effectiveness, accessibility, and sustainability of these intervention strategies. Graphical abstract

Effectiveness of Disinfectants Suitable for Inactivating SARS-CoV-2 at Cold-Chain Temperature - Xiaosong Wu; Yin Chen; Ling Wang; Xiling Guo; Lunbiao Cui; Yiming Shen; Fang Li; Hong Sun; Liubo Zhang; Jin Shen; Yan Xu (Food and Environmental Virology, 2022)

Rapid and sensitive identification of pleural and peritoneal infections by droplet digital PCR - Fangmei Zhou; Shoudong Sun; Xiling Sun; Ye Chen; Xuejing Yang (Folia Microbiologica, 2021)

Identification and genetic characterization of a novel circular single-stranded DNA virus in a human upper respiratory tract sample - Lunbiao Cui; Binyao Wu; Xiaojuan Zhu; Xiling Guo; Yiyue Ge; Kangchen Zhao; Xian Qi; Zhiyang Shi; Fengcai Zhu; Lixin Sun; Minghao Zhou (Archives of Virology, 2017)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)

Antioxidative and Cardioprotective Effects of Total Flavonoids Extracted from Dracocephalum moldavica L. Against Acute Ischemia/Reperfusion-Induced Myocardial Injury in Isolated Rat Heart - Jiangtao Jiang; Xuan Yuan; Ting Wang; Hongmei Chen; Hong Zhao; Xinyan Yan; Zhiping Wang; Xiling Sun; Qiusheng Zheng (Cardiovascular Toxicology, 2014)